A study to ascertain the patients' satisfaction of the quality of hospital care in Greece compared with the patients' satisfaction in Poland - Raftopoulos, Vasilios; Theodosopoulou, Eleni; Nikolaos, Triantafyliou (My University, 2007)
PURPOSE: The aim of this study is to evaluate the satisfaction of elderly patients, of the hospital care's quality, based on the literature evidence on results of a qualitative research and on a previous developed conceptual frame. MATERIAL AND METHODS: We developed the Elderly Patient Satisfaction Scale (EPSS) by using a combination of qualitative and quantitative research. In this study participated 320 elderly patients from Greece (182 male, 138 female) and 240 patients (136 male, 104 female) from Poland (mean age 74.16 +/- 6.14 years). Most of elderly patients were married. Inclusion criteria were: elderly patients over 65 years old, being able to be interviewed, hospitalized for at least three days and not to be suffering from severe mental disease. RESULTS: There was no correlation among age and global patients' satisfaction. Men in both of groups were expressed greater satisfaction with perceived quality of doctor care than women. Age positively correlated with question who estimate the satisfaction with the time that doctor spends for medical history taking. Patient's education correlated with question (satisfaction with availability of nurses night). Patient's depression found that affects the quality of hospital care and the satisfaction. Elderly patients were most satisfied with the technical care ability of nurse. The time period of hospital stay is correlated negatively with patient's global satisfaction. CONCLUSIONS: No significant difference between the patients from Greece and Poland in majority of dimensions: the satisfaction of elderly patients, of the hospital care's quality was noted.
Keywords: Medical care; Hospitals; Patient satisfaction; Poland; Greece